KOMUNIKASI PUBLIK HUMAS DINAS KOMUNIKASI DAN INFORMATIKA PROVINSI JAWA BARAT DALAM MENYAMPAIKAN INFORMASI KEPADA MASYARAKAT MELALUI MEDIA SOSIAL @HUMAS_JABAR TAHUN 2023 - Fahira Izzatuljannah; Ivan Darmawan; Agus Taryana (LPPM Universitas Abdurrab, 2024)
Public Relations has an important role in managing and improving public information services to the public, especially through Instagram social media. In line with technological developments and changes in people's communication behavior, the Public Relations of the West Java Province Communication and Information Service utilizes Instagram social media to carry out public communication and information services to the community. This phenomenon has a significant impact on the success felt by West Java Public Relations and the community. The aim of the research is to determine the success of public communication carried out by West Java Public Relations to the public in providing information and public services through the social media Instagram @humas_jabar. This research uses qualitative methodology to determine the success of West Java Public Relations public communication in providing public service information to the community via social media Instagram @humas_jabar. Qualitative analysis is used to analyze qualitative data and data collection is carried out through interviews, observation, documentation and literature study. The results of this research show that the public communication carried out by West Java Public Relations in providing public service information to the public via the social media Instagram @humas_jabar has been successful, and it is necessary to provide some education to increase this success so that the public can better understand the use of Instagram social media. as well as increasing clearer information regarding directions to the public to provide advice, responses and suggestions.